Implitapide, a Microsomal Triglyceride Transfer Protein Inhibitor, Reduces Progression of Atherosclerosis in Apolipoprotein E Knockout Mice Fed a Western-Type Diet: Involvement of the Inhibition of Postprandial Triglyceride Elevation - Ueshima, Koji; Akihisa-Umeno, Hitomi; Nagayoshi, Akira; Takakura, Shoji; Matsuo, Masahiko; Mutoh, Seitaro (Biological & Pharmaceutical Bulletin, 2005)
Microsomal triglyceride transfer protein (MTP) is essential for the synthesis of both chylomicron in the intestine and very low-density lipoprotein in the liver. An MTP inhibitor, (2S)-2-cyclopentyl-2-[4-[(2,4-dimethyl-9H-pyrido[2,3-b]indol-9-yl)methyl]phenyl]-N-[(1S)-2-hydroxy-1-phenylethyl]ethanamide (implitapide), has been shown to suppress atherosclerosis in apolipoprotein E knockout (apoE KO) mice. To elucidate the antiatherosclerotic mechanisms of implitapide in the mice, we examined the effects on plasma lipid levels, triglyceride (TG) elevation after oral fat loading, and development of atherosclerosis in apoE KO mice fed a Western-type diet. Implitapide at a dosage of approximately 3.2 mg/kg/day significantly reduced both total cholesterol and TG levels during the 8-week treatment period. In addition, implitapide significantly inhibited the increase in plasma TG levels after oral olive oil loading tests conducted after 4 weeks of treatment. After the treatment, implitapide significantly suppressed the atherosclerotic lesion area by 83% compared with a control group. These results provide direct evidence that the antiatherosclerotic effects of implitapide in apoE KO mice are associated with the inhibition of postprandial TG elevation, in addition to the reduction of both plasma total cholesterol and TG levels.